Spatiotemporal and demographic characteristics of scrub typhus in Southwest China, 2006–2017: An analysis of population‐based surveillance data. Issue 4 (6th February 2020) - Xin, Hualei; Sun, Junling; Yu, Jianxing; Huang, Jilei; Chen, Qiulan; Wang, Liping; Lai, Shengjie; Clements, Archie C. A.; Hu, Wenbiao; Li, Zhongjie
Abstract: Scrub typhus is a life‐threatening vector‐borne disease. During the past decade, the number of areas affected by this disease has expanded in many countries. In this study, we aim to identify the spatiotemporal and demographic characteristics of scrub typhus in Southwest China, an emerging endemic region for scrub typhus. Population‐based surveillance data capturing scrub typhus cases in two provinces of Southwest China during 2006–2017 were retrieved. Descriptive temporal and spatial analyses were conducted and stratified by age group. The space‐time scan statistic was used to identify spatiotemporal clusters of scrub typhus occurrence at the county level. During the study period, 30, 001 scrub typhus cases were recorded in Southwest China, with a total of 61.0% (191/313) of counties being affected; most cases (94.3%) occurred in rural areas. The annual incidence rate increased substantially from 0.25/100, 000 in 2006 to 5.38/100, 000 in 2017 (>21‐fold change). The 0‐ to 4‐year‐old and 45‐ to 64‐year‐old subgroups had the highest cumulative incidence rates (57.46 and 32.98/100, 000, respectively). Furthermore, since 2006, the 0‐ to 4‐year‐old (slope = 0.83, p < .01) and 45–64‐year‐old (slope = 0.69, p < .01) age groups have had the highest increases in incidence of all age groups. The most likely spatial cluster of overall cases (relative risk = 4.13, p < .01) occurred in the southern region of Southwest China and included 41 high‐risk counties. In conclusion, scrub typhus appears to be widely distributed and rapidly increasing in Southwest China. Young children and middle‐aged adults were the most severely affected groups, and the disease appeared to predominantly cluster in the southern part of Southwest China. Further in‐depth surveys to determine the epidemiological characteristics and driving factors of this emerging disease and to facilitate effective control programmes among high‐risk groups in the affected areas should be promoted.